ANALISIS METODE PENYELESAIAN PEMBIAYAAN MURABAHAH BERMASALAH PADA PT. BANK ACEH SYARIAH KCP LABUHAN HAJI - Ona Suarnidar; Nevi Hasnita; yulindawati yulindawati (Prodi Perbankan Syariah FEBI UIN Ar-Raniry, 2022)
Non-performing financing is one of the major risks faced by banks. The larger the non-performing financing, the worse it will be on the soundness of bank liquidity. This research is a qualitative research. The method used in this study is a descriptive qualitative method of analysis with a field approach through interviews and documentation. The results of the study explain that the factors that cause problematic murabahah financing consist of internal factors, namely bank management errors and external factors, namely mistakes from financing customers. The methods used to resolve problematic murabahah financing are mentoring, financing restructuring, foreclosure of collateral, and execution of guarantees